Cannabinoid CB2 Receptor Mediates Nicotine-Induced Anti-Inflammation in N9 Microglial Cells Exposed to β Amyloid via Protein Kinase C - Ji Jia; Jie Peng; Zhaoju Li; Youping Wu; Qunlin Wu; Weifeng Tu; Mingchun Wu (Hindawi Limited, 2016)
Background. Reducing β amyloid- (Aβ-) induced microglial activation is considered to be effective in treating Alzheimer's disease (AD). Nicotine attenuates Aβ-induced microglial activation; the mechanism, however, is still elusive. Microglia could be activated into classic activated state (M1 state) or alternative activated state (M2 state); the former is cytotoxic and the latter is neurotrophic. In this investigation, we hypothesized that nicotine attenuates Aβ-induced microglial activation by shifting microglial M1 to M2 state, and cannabinoid CB2 receptor and protein kinase C mediate the process. Methods. We used Aβ1-42 to activate N9 microglial cells and observed nicotine-induced effects on microglial M1 and M2 biomarkers by using western blot, immunocytochemistry, and enzyme-linked immunosorbent assay (ELISA). Results. We found that nicotine reduced the levels of M1 state markers, including inducible nitric oxide synthase (iNOS) expression and tumor necrosis factor α (TNF-α) and interleukin- (IL-) 6 releases; meanwhile, it increased the levels of M2 state markers, including arginase-1 (Arg-1) expression and brain-derived neurotrophic factor (BDNF) release, in the Aβ-stimulated microglia. Coadministration of cannabinoid CB2 receptor antagonist or protein kinase C (PKC) inhibitor partially abolished the nicotine-induced effects. Conclusion. These findings indicated that cannabinoid CB2 receptor mediates nicotine-induced anti-inflammation in microglia exposed to Aβ via PKC.